Circulating immune cell dynamics in patients with triple negative breast cancer treated with neoadjuvant chemotherapy. (5th August 2020) - Talamantes, Sarah; Xie, Eric; Costa, Ricardo L. B.; Chen, Melissa; Rademaker, Alfred; Santa‐Maria, Cesar A.
Abstract: Background: Lymphopenia has been associated with inferior cancer outcomes, but there is limited data in breast cancer. We describe the effects of neoadjuvant chemotherapy on circulating immune cells and its association with pathological complete response (pCR) rates in triple negative breast cancer (TNBC). Methods: We constructed a database of patients with early stage TNBC treated with neoadjuvant chemotherapy. Circulating lymphocytes and monocytes were assessed before and after neoadjuvant chemotherapy. These were correlated with pCR rates and disease‐free survival (DFS) using Fisher's exact test, logistic regression, and the log‐rank test. Results: From 2000 to 2015, we identified 95 eligible patients. Median age was 50; 29 (31%) were treated with platinum‐containing chemotherapy; and 66 (69%) with nonplatinum‐containing chemotherapy (anthracycline‐taxane, or either alone). About 32 (34%) patients achieved a pCR; and 33 (35%) had recurrence events. Median follow‐up time was 47 months. No significant associations were found between changes in lymphocytes and pCR or DFS. There was a correlation between lower monocyte levels after neoadjuvant chemotherapy and pCR (mean monocyte 0.56 in those with no‐pCR vs 0.46 in those with pCR, P = .049, multivariate P = .078) and DFS (median DFS in highest monocyte quartile was 30 vs 107 months in lowest quartile, P = .022, multivariate P = .023). In patients who received nonplatinum regimens, DFS was better among those who had larger decreases in monocytes. Conclusions: Development of lymphopenia from neoadjuvant chemotherapy was not associated with pCR in patients with TNBC. However, lower absolute circulating monocytes after neoadjuvant chemotherapy was associated with improved outcomes. Abstract : Development of lymphopenia from neoadjuvant chemotherapy was not associated with pathological complete response in patients with triple negative breast cancer. However, lower absolute circulating monocyte counts after neoadjuvant chemotherapy were associated with improved clinical outcomes.